PENGARUH LESUNYA INDUSTRI MEBEL TERHADAP KELUARGA PENGUSAHA MEBEL WANITA DI JEPARA - Fitri Ella Fauziah; Bening Kristyassari; Sri Mulyani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
Furniture crisis make almost all furniture entrepreneurs in Jepara have the influences. Woods prices and others material’s have increasing, but in the other side it is not supported by the increasing sales prices because the customers didn’t want to increase the price so it will reduce their income. Crisis became a burden to women entrepreneur. Women entrepreneurs have a double role, in their occupation and in their household. In this paper we try to examine the influence of furniture to the family of women entrepreneur. That is education, health, food pattern, and relationship between family member, family consumption degree and others.This paper is using the qualitative methods. Population includes all women entrepreneur in Jepara regency. We took the sample by using snowball sampling. Based on survey we found 20 respondents, that include craftsman, sawmill, broker on local (domestic) or export.This paper result that women entrepreneur may survive on furniture crisis depends on size of their company, their personal skills and product sales destiny. For example: export to Europe has reduced, but in the other side export to Malaysia were increased. The other result that during furniture crisis, the women entrepreneurs still gave priority to education of their children’s, although how hard is. The other factors as health, food pattern, and family consumption degree a little bit reduced. For the recreation their still did that but with specific limits. The relationship between family members became not to harmonic.